Clock dance - Tyler, Anne (New York : Alfred A. Knopf, 2018)
Willa Drake can count on one hand the defining moments of her life: when she was 11 and her mother disappeared, being proposed to at 21, the accident that would make her a widow at 41. At each of these moments, Willa ended up on a path laid out for her by others. So when she receives a phone call telling her that her son's ex-girlfriend has been shot and needs her help, she drops everything and flies across the country. The spur-of-the moment decision to look after this woman - and her nine-year-old daughter, and her dog - will lead Willa into uncharted territory. Surrounded by new and surprising neighbours, she is plunged into the rituals that make a community, and takes pleasure in the most unexpected things.
Keywords: Drake, Willa, -- (fiktiivinen hahmo); romaanit; kaunokirjallisuus -- englanninkielinen kirjallisuus